2016
DOI: 10.1186/s12885-016-2269-2
|View full text |Cite
|
Sign up to set email alerts
|

Severe myositis of the hip flexors after pre-operative chemoradiation therapy for locally advanced rectal cancer: case report

Abstract: BackgroundThe use of neoadjuvant radiation therapy and chemotherapy in the treatment of locally advanced rectal adenocarcinoma has been shown to reduce disease recurrence when combined with surgery and adjuvant chemotherapy. We report a case of a patient who developed a debilitating bilateral myopathy of the hip flexors after successful treatment for rectal cancer. To the best of our knowledge, this is the first such complication from radiation therapy reported in a patient with colorectal cancer. The dispropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…No evidence of infection was found in our case with a normal range of inflammatory markers. Chemoradiation causing myopathy of hip muscles was reported by Florczynski et al 6 in a case of adenocarcinoma of the rectum. That happened 5 month post-radiotherapy and 2 month post-chemotherapy completion in their case.…”
Section: Discussionmentioning
confidence: 81%
“…No evidence of infection was found in our case with a normal range of inflammatory markers. Chemoradiation causing myopathy of hip muscles was reported by Florczynski et al 6 in a case of adenocarcinoma of the rectum. That happened 5 month post-radiotherapy and 2 month post-chemotherapy completion in their case.…”
Section: Discussionmentioning
confidence: 81%
“…Proposed mechanisms include lowering of the inflammatory threshold in radiated tissues, and enhanced drug hypersensitivity [13,14]. Subclinical inflammatory processes and tissue damage caused by RT presenting clinically only after additional toxicity caused by chemotherapy is another possibility [15].…”
Section: Discussionmentioning
confidence: 99%
“…Few reports exist of RRR associated with 5FU and oxaliplatin, and myositis is even more rare. Specifically, only one other publication has described RRR myositis following administration of 5FU and oxaliplatin [15].…”
Section: Discussionmentioning
confidence: 99%
“…[ 63 ] Furthermore, chemotherapy has potential to exacerbate tissue injury caused by radiation therapy, phenomenon known as radiation recall. [ 64 ] In such cases, previously irradiated tissue becomes more vulnerable to toxic effect of subsequent systemic therapy. Radiation recall most commonly occurs as dermatitis but could also leads to myositis, pneumonitis, or enterocolitis.…”
Section: Musculoskeletalmentioning
confidence: 99%
“…Radiation recall most commonly occurs as dermatitis but could also leads to myositis, pneumonitis, or enterocolitis. [ 64 65 66 67 ] Time interval between radiation treatment and radiographic appearance of radiation-induced muscle changes have been studied with both photon and neutron therapy. MR imaging showed that muscle edema following radiation therapy with neutrons peaks at about 6 months compared to 12–18 months after treatment with photons.…”
Section: Musculoskeletalmentioning
confidence: 99%